2007
DOI: 10.1111/j.1439-0523.2007.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of breeding biofortified pearl millet with high grain iron and zinc content

Abstract: Development of crop cultivars with elevated levels of micronutrients is being increasingly recognized as one of the approaches to provide sustainable solutions to various health problems associated with micronutrient malnutrition, especially in developing countries. To assess the prospects of this approach in pearl millet (Pennisetum glaucum), a diverse range of genetic materials, consisting of 40 hybrid parents, 30 each of population progenies and improved populations, and 20 germplasm accessions, was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
63
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 5 publications
13
63
3
Order By: Relevance
“…A negative association may pose problems for breeding of seed mineral-dense cultivars with high seed yield per se. Seed weight in pearl millet is highly significant and positively associated with seed Fe (r ¼ 0.80) and Zn (r ¼ 0.85) (Velu et al 2007), while it is significant and positively correlated (r ¼ 0.61) with Fe in common bean (Gelin et al 2007). …”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 99%
“…A negative association may pose problems for breeding of seed mineral-dense cultivars with high seed yield per se. Seed weight in pearl millet is highly significant and positively associated with seed Fe (r ¼ 0.80) and Zn (r ¼ 0.85) (Velu et al 2007), while it is significant and positively correlated (r ¼ 0.61) with Fe in common bean (Gelin et al 2007). …”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 99%
“…It is a major source of mineral micronutrients in several African countries as well. Results of a preliminary study have shown large variability for grain Fe and Zn among breeding lines and populations as well as within the populations (Velu et al 2007). An understanding of the nature of gene action and heterosis would be a significant input into designing effective breeding strategies for the development of OPVs and hybrids.…”
Section: Introductionmentioning
confidence: 96%
“…Initial screening of germplasm accessions found ranges of 30-76 ppm iron (and 25-65 ppm zinc) in pearl millet, nearly reaching the full breeding target of 77 ppm (that is, an increment of +30 ppm additional grain iron compared to 47 ppm on average in non-biofortified germplasm). High-iron genotypes were selected to initiate crosses [62,63]. High correlation between iron and zinc content indicated good prospects for simultaneous selection for the two micronutrients [64,65,66].…”
Section: Iron Pearl Milletmentioning
confidence: 99%